(untitled) (Research, Society and Development, 2020)
The present study aimed to evaluate the use of the babassu decomposed stem under different proportions in substrate composition for the vegetative propagation of Euphorbia splendens. The experiment was conducted in a greenhouse and we used a completely randomized design with six treatments and four repetitions. Six types of substrates were formulated using a mixture of babassu decomposed stem (BDS) and soil (SL) in the proportions of 100% SL, 20:80 % BDS:SL, 40:60 %, BDS:SL, 60:40 % BDS:SL, 80:20 % BDS:SL and 100 % BDS. The seedlings were evaluated at 45 days after cutting by measuring the diameter of the longest shoot, number of leaves, number of shoots, root length, root volume, largest shoot length, fresh weight of the aerial part, root fresh weight, dry weight of the aerial part, and root dry weight. The treatments that presented normality and homoscedasticity were submitted to simple linear regression analysis. The proportion of the substrate of 20: 80% BDS: SL has a greater length of the largest shoot about the substrate 80:20% BDS: SL. The diameter of the largest sprout, the number of leaves, and the root length decreased due to the increase in the proportion of babassu decomposed stem in the substrates. The production of seedlings using cuttings of Euphorbia splendens is facilitated by the fact that it is a species with easy rooting, therefore, it is not necessary to use substrates with proportions of babassu decomposed stem and soil for its vegetative propagation.